The relationship between organizational culture and employees' job performance at Proton Tanjung Malim Sdn Bhd / Nur Awanis Zulkifli - Zulkifli, Nur Awanis (Faculty of Business and Management, 2018)
This research has been concluded to identify the relationship between organizational culture and employees' job performance at PROTON Tanjung Malim Sdn Bhd. This research has four research questions which are the level of overall organizational culture, organizational culture trait has the highest level of implementation among employees, the level of overall job performance of employees and the relationship between organizational culture and employees' job performance at PROTON Tanjung Malim Sdn Bhd. The scopes of this research are focused on 60 number of population. The sample sizes taken are 54 respondents as referred to the size for a given population by Krejeie and Morgan (1970). The sampling technique used is simple random sampling. The research findings can be concluded that there is positive relationship between four traits of organizational culture and employees' job performance PROTON Tanjung Malim Sdn Bhd.